Problemy przekładu polsko-angielskiego testamentów i dokumentów prawa spadkowego. Studium przypadku - Matulewska, Aleksandra (Investigationes Linguisticae, 2009)
This paper deals with the analysis of language and translation mistakes and errors in the translation of Polish testaments into English. This article presents a selection of examples from the translation assignments of students of the postgraduate School of Translation, Interpreting and Foreign Languages at Adam Mickiewicz University. The author presents incorrect translations into English and explains why they are not proper in the translative situation. The examples are illustrated with the author’s suggestions of correct equivalents. There is also a short description of the spotted types of language and translation errors and mistakes. The identified problems result from the translation method applied (which is not always properly chosen), syntactic and grammatical differences between Polish and English, as well as culturally-conditioned differences in Polish and English legal realities.